ʺInnovative Competence of the Future Hospitality Specialist as a Modern Employer’s Requirementʺ - Oliinyk, N.; Podolskyi , M. (Problems of Engineer-Pedagogical Education, 2024)
dern employers in the hospitality industry. The hospitality industry is one of the most dynamic and important sectors of the world economy, covering the hotel business, restaurant business, tourism and entertainment. This industry is directly related to meeting people's needs for accommodation, food, recreation and travel, and, as a result, is constantly influenced by changes in consumer preferences, technology, the global economy and socio-cultural trends. Today, the hospitality industry faces a number of challenges that require changes in the way it operates and manages. Based on the analysis of scientific literature, the Standards of Higher Education in the specialties 241 Hotel and Restaurant Business, 242 Tourism, 181 Food Technologies and the results of a survey of employers, an ideal profile of a hospitality specialist has been created, which harmoniously combines technical knowledge, service skills, managerial skills and personal qualities. An ideal hospitality specialist is a professionally trained person with appropriate education, developed professional and soft skills, who constantly strives for self-improvement and is ready to meet the challenges of the modern hospitality market. It is proved that innovative competence is one of the key places in the professional model of a hospitality specialist. The innovative competence of a future hospitality specialist is defined as a complex integral intellectual, professional and personal formation, which is formed in the process of professional training of students in a higher education institution, manifests itself, develops and improves in professional activities, and the effectiveness of professional activity significantly depends on the types of theoretical, practical and psychological readiness of a specialist for it. The paper proposes a model of innovative competence of a future hospitality specialist, which includes the following components: understanding of industry trends, technological competence, strategic thinking, creativity and design thinking, change management. The proposed model is generalized and can be used both in education and in organizations. Teachers can use it as a tool for reflection to improve the understanding of innovation competence among students, as well as a basis for developing a curriculum and practically oriented guidelines for the development of innovation competence in future hospitality professionals. Organizations can use this model to support the recruitment of professionals with developed innovation competence, assess and develop innovation competence among employees, and form innovation teams.